Solve the equation: -4 (3-x) = 3 (4x-6)

Israel Hale 2022-08-01 Answered
Solve the equation: 4 ( 3 x ) = 3 ( 4 x 6 )
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (1)

Wayne Everett
Answered 2022-08-02 Author has 19 answers
Step 1
Given: 4 ( 3 x ) = 3 ( 4 x 6 )
Step 2
Now, 12 + 4 x = 12 x 18 4 x 12 x = 18 + 12 8 x = 6 8 x = 6 x = 6 8 x = 3 4
Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

New questions